A realistic human head phantom for electromagnetic detection of brain diseases - Zelin Bai; Diyou Chen; Ke Ma; Gui Jin; Jinlong Qiu; Quanquan Li; Haocheng Li; Mingsheng Chen (PeerJ)
The research on electromagnetic detection technology for brain diseases requires precise simulation of the human head. This article combines high-precision computed tomography (CT) images and magnetic resonance imaging (MRI) images to establish an electromagnetic numerical model of the human head with a real anatomical structure. (1) It had Asian characteristics and encompassed 14 different structures, including skin, muscles, cranial bones, cerebrospinal fluid, cerebral veins, cerebral arteries, gray matter, white matter of the brain, basal ganglia, thalamus, cerebellum, brainstem, eyeballs, and vertebrae. (2) The model used a combination of 0.625 mm-resolution CT and 1 mm-resolution MRI image data for reconstruction, with a smooth surface and high accuracy. (3) Within the simulation environment, this model enabled the generation of various brain disease scenarios, such as different types and degrees of cerebral hemorrhage and cerebral ischemia. It proved valuable for studying the distribution of electromagnetic fields in the human head and for investigating novel electromagnetic detection techniques exploiting brain tissue dielectric properties. (4) The created physical model and the numerical model were derived from the same person, which provided a good continuity between simulation experiments and physical experiments, and provided a realistic verification platform for the research of electromagnetic detection technology for brain diseases, such as differentiating the kind of stroke, monitoring brain edema, brain tumor microwave imaging, and diagnosis of Alzheimer’s disease.